(untitled) (Global Journal of Science Frontier Research, 2012)
Studies were conducted for three beekeeping seasons (between 2009 and 2011) on 400 colonized hives sited in the two major vegetation zones of Nigeria. Direct counting of the number of sting babels deposited on the beekeepers kit by scout bees defending her colony was done during the period of routing inspection and harvesting of crops from selected colonies while swarming and abscondment of established colonies after the first visit was noted and recorded for each farm. Behaviourial variations of mellifera species from the forest and savannah vegetation zones of Nigeria revealed that majority (above 65%) of the honeybees were highly aggressive and none of the colonies in the country was stingless. The preponderance of the deposit of the sting babels by the scout bees in the nation was highly aggressive +++> aggressive ++ > less aggressive + >stinglessness -. Comparison of behaviourial variations of Apis mellifera colonies in Nigeria revealed that Abuja (31.3%), Adamawa (4.0%) and Osun (3.3%) States had the less aggressive species of honeybees while, both Kebbi (80.7%) and Ebonyi (79.7%) States recorded the highest percentages of sting babels deposition in the savannah and forest vegetation respectively.